Pengaruh Kompensasi Finansial dan Non Finansial terhadap Kinerja Karyawan Mesastila Hotels dan Resorts - Priyatono, Margo (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2019)
This study aims to determine the effect of financial and non-financial compensation on the performance of Mesastila Hotels & Resorts Magelang employees which are expected to be useful for management in improving the performance of their employees. This research method uses a survey approach to employees with a media questionnaire which is then analyzed by instrument and variable feasibility test, multiple linearity and different test based on employee status (fixed and contract). The results of this study indicate that financial and non-financial compensation has a significant effect on employee performance. Therefore management can provide rewards in the form of direct (financial) or indirect (non-financial) to its employees. Because someone's attitude reflects the extent to which an employee knows and is bound to his organization and reflects employee loyalty to the organization and the ongoing process in which members of the organization express their concern for the organization and continued success and progress.